1992
DOI: 10.1152/ajpcell.1992.263.3.c590
|View full text |Cite
|
Sign up to set email alerts
|

The iodide channel of the thyroid: a plasma membrane vesicle study

Abstract: The uptake of radioactive iodide or chloride by plasma membrane vesicles of bovine thyroid was studied by a rapid filtration technique. A Na(+)-I- cotransport was demonstrated. When this Na(+)-I- cotransport is inactive (i.e., at 4 degrees C and in the absence of Na+), an uptake of iodide above chemical equilibrium could be induced, driven by the membrane potential. The latter was set up by allowing potassium to diffuse into the membrane vesicles in the presence of valinomycin and of an inward K+ gradient. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…It is worth noting that this property is one of the major characteristics of dog thyroid cells in primary culture (28). The increased release of 99m TcO 4 Ϫ from the Ca 2ϩ ionophore-stimulated ANO1-expressing HEK 293T and PCCl3 cells is consistent with the very low affinity but sizeable effect of ClO 4 Ϫ , the chemical analog of TcO 4 Ϫ , on the high affinity iodide channel from bovine thyroid membrane vesicles (13,14). A stimulatory effect of Ca 2ϩ ionophore on iodide efflux had already been observed in the FRTL-5 rat thyroid cell line (43).…”
Section: Discussionsupporting
confidence: 54%
“…It is worth noting that this property is one of the major characteristics of dog thyroid cells in primary culture (28). The increased release of 99m TcO 4 Ϫ from the Ca 2ϩ ionophore-stimulated ANO1-expressing HEK 293T and PCCl3 cells is consistent with the very low affinity but sizeable effect of ClO 4 Ϫ , the chemical analog of TcO 4 Ϫ , on the high affinity iodide channel from bovine thyroid membrane vesicles (13,14). A stimulatory effect of Ca 2ϩ ionophore on iodide efflux had already been observed in the FRTL-5 rat thyroid cell line (43).…”
Section: Discussionsupporting
confidence: 54%
“…chloride channels, or a second iodide channel. It is noteworthy that studies performed with plasma membrane vesicles suggested the existence of two apical iodide channels (41). One of these channels appears to display a high permeability and specificity for iodide (K m ϳ70 M), whereas the second anion channel has a lower affinity for iodide (K m ϳ33 mM) (41).…”
Section: ) Similar Results Were Observed In Tsa-293 Cells (Results mentioning
confidence: 99%
“…It is noteworthy that studies performed with plasma membrane vesicles suggested the existence of two apical iodide channels (41). One of these channels appears to display a high permeability and specificity for iodide (K m ϳ70 M), whereas the second anion channel has a lower affinity for iodide (K m ϳ33 mM) (41). The pendrin-mediated apical iodide transport shown here, together with the loss of function of pendrin mutations, strongly suggest that pendrin corresponds to one of these channels.…”
Section: ) Similar Results Were Observed In Tsa-293 Cells (Results mentioning
confidence: 99%
“…It was demonstrated to function as an iodide transporter (Taylor et al, 2002;Yoshida et al, 2002). Electrophysiological studies suggest the existence of two apical iodide channels (Golstein et al, 1992), and as recently shown, pendrin mediating vectorial iodide transport corresponds to one of these channels (Gillam et al, 2004). The pendrin gene is not under the control of TSH but it is upregulated by thyroglobulin (Royaux et al, 2000).…”
mentioning
confidence: 96%